Redescription of Moenkhausia doceana (Steindachner, 1877) (Ostariophysi: Characiformes): a characid from the Northeastern Mata Atlântica ecoregion, Brazil - Carvalho, Fernando R.; Sarmento-soares, Luisa M.; Martins-pinheiro, Ronaldo F. (Sociedade Brasileira de Ictiologia, 2014)
Moenkhausia doceana is redescribed from the Northeastern Mata Atlântica ecoregion drainages in Espírito Santo, Minas Gerais, and Bahia states. The species is distinguished from its congeners by a long anal fin, with 29-34 (mode 32) branched rays; 4-7 (mode 5) maxillary teeth; and 7-8 (mode 7) scale rows above lateral line at dorsal-fin origin. Phylogenetic hypothesis about its relationships among the Characidae is also presented and commented.

Moenkhausia doceana é redescrita das drenagens da ecorregião Mata Atlântica Nordeste nos estados do Espírito Santo, Minas Gerais e Bahia. A espécie distingue-se das demais congêneres por apresentar uma nadadeira anal longa, com 29-34 (moda 32) raios ramificados; 4-7 (moda 5) dentes maxilares e 7-8 séries horizontais de escamas acima da linha lateral até a origem da nadadeira dorsal. Hipótese filogenética sobre suas relações em Characidae é também apresentada e comentada.
Keywords: Characidae; Lambari; Rio Doce; Systematics; Tetragonopterus